Ni/Ru–Mn/Al2O3 catalysts for steam reforming of toluene as model biomass tar. (February 2016) - Oh, Gunung; Park, Seo Yoon; Seo, Myung Won; Kim, Yong Ku; Ra, Ho Won; Lee, Jae-Goo; Yoon, Sang Jun
Abstract: The catalytic steam reforming of the major biomass tar component, toluene, was studied over two commercial Ni-based catalysts and two prepared Ru–Mn-promoted Ni-base catalysts, in the temperatures range 673–1073 K. Generally, the conversion of toluene and the H2 content in the product gas increased with temperature. A H2 -rich gas was generated by the steam reforming of toluene, and the CO and CO2 contents in the product gas were reduced by the reverse Boudouard reaction. A naphtha-reforming catalyst (46-5Q) exhibited better performance in the steam reforming of toluene at temperatures over 873 K than a methane-reforming catalyst (Reformax 330). Ni/Ru–Mn/Al2 O3 catalysts showed high toluene reforming performance at temperatures over 873 K. The results indicate that the observed high stability and coking resistance may be attributed to the promotional effects of Mn on the Ni/Ru–Mn/Al2 O3 catalyst. Highlights: Toluene was subjected to steam reforming over Ni-based catalysts. Based on commercial catalyst results, Ni/Ru–Mn/Al2 O3 catalysts were prepared. The best conversion and H2 contents were achieved with Ni/Ru–Mn (2.6 wt%)/Al2 O3 . This catalyst showed the best stability and coking resistance promoted by Mn. The major H2 generation pathway occurred through steam reforming reactions.